2004
DOI: 10.1111/j.1432-1033.2004.04059.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the in planta antiviral activity of elderberry ribosome‐inactivating proteins

Abstract: Although the type-2 ribosome-inactivating proteins (SNA-I, SNA-V, SNLRP) from elderberry (Sambucus nigra L.) are all devoid of rRNA N-glycosylase activity towards plant ribosomes, some of them clearly show polynucleotideadenosine glycosylase activity towards tobacco mosaic virus RNA. This particular substrate specificity was exploited to further unravel the mechanism underlying the in planta antiviral activity of ribosome-inactivating proteins. Transgenic tobacco (Nicotiana tabacum L. cv Samsun NN) plants expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Indeed, some protection from some viruses was conferred to transfected plants by several type 1 RIPs [reviewed in refs 144,145]. and, although with less efficiency, by type 2 RIPs from S. nigra, SNA-I'[147] and SNA-V[148], but not by SNA-If from the same plant[149]. High-level expression of PAP was…”
mentioning
confidence: 99%
“…Indeed, some protection from some viruses was conferred to transfected plants by several type 1 RIPs [reviewed in refs 144,145]. and, although with less efficiency, by type 2 RIPs from S. nigra, SNA-I'[147] and SNA-V[148], but not by SNA-If from the same plant[149]. High-level expression of PAP was…”
mentioning
confidence: 99%
“…Although type 2 RIPs are sequestered from the host ribosomes in plant cells in, e.g., vacuoles and intercellular spaces, it can be envisaged that once the plant is attacked by pathogens the type 2 RIPs Plant Toxins DOI 10.1007/978-94-007-6728-7_4-1 # Springer Science+Business Media Dordrecht 2015 could enter the plant cytosolic compartments. However, for several type 2 RIPs such as SNA-I, SNA-V, and SNLRP it was reported that they are inactive on plant ribosomes (Vandenbussche et al 2004a). …”
Section: Role Of Type 2 Rips In Plant Defensementioning
confidence: 97%
“…Although there is no doubt about the antiviral activity of RIPs, their mode of action has not been elucidated. With respect to the RIP antiviral activity, two major hypotheses have been proposed (Vandenbussche et al 2004a). (i) The RIPs can directly work on virus nucleic acids by their N-glycosidase activity or polynucleotide:adenosine glycosidase activity.…”
Section: Antiviral Activity Of Type 2 Ripsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to type-1 RIPs, the antiviral activity of type-2 RIPs has been far less documented. Several type-2 RIPs were demonstrated to exhibit in vitro or in vivo antiviral activity (Stevens et al 1981;Kumar et al 1993) but, so far in planta antiviral activity has been reported only for type-2 RIPs from Sambucus nigra (Chen et al 2002a;Vandenbussche et al 2004). …”
Section: Introductionmentioning
confidence: 95%